microRNA-122 amplifies hepatitis C virus translation by shaping the structure of the internal ribosomal entry site - Schult, Philipp; Roth, Hanna; Adams, Rebecca L.; Mas, Caroline; Imbert, Lionel; Orlik, Christian; Ruggieri, Alessia; Pyle, Anna M.; Lohmann, Volker (Nature Communications, 2018)
The liver-specific microRNA-122 is an essential proviral host factor of Hepatitis C virus replication. Here the authors show that microRNA-122 functions as an RNA chaperone that guides the formation of a functional internal ribosome entry site by preventing energetically more favorable secondary structures within the HCV RNA genome.
Gesehen am 27.08.2019